PENGARUH REWARD DAN PUNISHMENT TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS IV SDUT BUMI KARTINI JEPARA - Aan Widiyono; Dzurriyatin Thoyyibah; Abdulloh Haris Khoirun Nasir; M. Lutfi Hidayatullah (Universitas Islam Nahdlatul Ulama Jepara, 2019)
This research aims to study the presence or absence between the awarding and encouragement of mathematics learning outcomes for grade IV students of SDUT Bumi Kartini Mulyoharjo Jepara and increasing the contribution of providing assistance and punishment to the learning outcomes. The method used is ex post facto research. The sample of this student Yunani class IV students who were 26 students. The sampling technique used is nonprobabbility sampling with purposive sampling. Data collection was carried out using a questionnaire. Research result data shows that there is a significant influence between reward and punishment on mathematics learning outcomes of grade IV students. Because t arithmetic 3.167> t table 2.060 and with a significance test known significance value of 0.004 <0.005 then Ho is rejected and Ha is accepted, which means there is an influence between reward and punishment variables on students' mathematics learning outcomes.The coefficient number of determination (R Square) 0.304 is defined that reward and punishment can influence to student learning outcome 30.4% and the rest is 69.6% influenced by other unlisted variables.